Comparative Analysis of Governmental Systems: Assessing Democracy in Indonesia’s Presidential System and France’s Semi-Presidential System - Zainurohmah, Zainurohmah; Josephine, Emma (Indonesian State Law Review (ISLRev), 2023)
This paper conducts a comprehensive comparative analysis of governmental systems to assess the democratic principles inherent in Indonesia's Presidential System and France's Semi-Presidential System. Employing a normative juridical research method with a statutory, conceptual, and comparative approach, the study unveils the distinct features of each system and their implications for democratic governance. The research reveals similarities and differences in power distribution, emphasizing the commonality of the trias politica concept in both countries, albeit with unique characteristics. Notably, the divergence lies in the roles of state leaders: Indonesia designates the president as both head of state and government, whereas in France, the president is the head of state, and the prime minister assumes the role of head of government. Through this analysis, the paper aims to contribute to the field of comparative constitutional law and deepen our understanding of how different governmental structures impact the democratic fabric of nations.